It’s Not You, It’s Them: Quiet Quitting and the Influence of Organizational Justice, Work Engagement and Commitment – The Case of Employees in Education - Veronica R. Gamboa (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Organizations are, in hindsight, facing an economic crisis due to quiet quitting. This is a quantitative cross-sectional study on the antecedents of quiet quitting: perceived organizational justice (distributive, procedural, interpersonal, and informational), work engagement, and organizational commitment (affective, normative, and continuance). A total of 229 samples were collected from five private primary and secondary educational institutions in the Philippines, of which 180 qualified for data analysis. Data were collected from employees with 12 months of service in their institution. Multiple linear regression using JASP was utilized for data analysis. The results show that low work engagement, low affective commitment, and high continuance commitment are the predictors most likely to predict quiet quitting, whereas perceived distributive, procedural, interpersonal, and informational justice, as well as normative commitment, are not. This study contributes to new knowledge on the antecedents of quiet quitting in the context of education. The results of this study serve as input for policy development and interventions of school administrators and human resource practitioners.